2007
DOI: 10.1017/s002185960700754x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of promising genotypes based on path and cluster analyses

Abstract: SU MMARYThe objective of the present paper was to propose a statistical approach to support selection of the most promising genotypes in a breeding programme. The approach is based on applying two state-of-the-art statistical methodologies, likelihood-based path analysis and model-based cluster analysis. The first method is applied to find a causal mechanism lying behind a biological process of development of final crop yield. These results are then used for weighting traits to be used in cluster analysis, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…The earlier studies conducted with grass pea in Poland indicated that a normal rainfall level recorded during a year assures a plant height above 80 cm (Rybiński 2003). In 2002 at the 516 mm precipitation level, the grass pea mutant height was found within 67.8-94.3 cm but in 2003, a particularly dry period (331 mm), plant height ranged from 25.6 to 42.7 cm (Kozak et al 2008). Relatively low plant height and uniform maturity of plants observed in the present research was associated with a strong abiotic stress caused by the long-term drought.…”
Section: Diversity Of Morphological Traits and Geographic Trendsmentioning
confidence: 44%
“…The earlier studies conducted with grass pea in Poland indicated that a normal rainfall level recorded during a year assures a plant height above 80 cm (Rybiński 2003). In 2002 at the 516 mm precipitation level, the grass pea mutant height was found within 67.8-94.3 cm but in 2003, a particularly dry period (331 mm), plant height ranged from 25.6 to 42.7 cm (Kozak et al 2008). Relatively low plant height and uniform maturity of plants observed in the present research was associated with a strong abiotic stress caused by the long-term drought.…”
Section: Diversity Of Morphological Traits and Geographic Trendsmentioning
confidence: 44%
“…The previous studies on grass pea in Poland indicated that at normal annual rainfall amount about 600 mm (Dmochowska 2011), the plant height can be over 80 cm (Rybiński 2003). In 2002, at 516 mm rainfall level, plant height of grass pea mutants ranged from 67.8 up to 94.3 cm but in 2003, exceptionally dry (331 mm), it oscillated between 25.6 and 42.7 cm (Kozak et al 2008). Relatively low plant height (from 37.2 to 63.6 cm) and uniform maturity of plants were observed in the experiment in 2006 and associated with strong abiotic stress caused by long term drought (Grela et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Path analysis has been very popular in various fields, agriculture not being an exception (e.g., Lakshmi andPadma 2011, Maleki et al 2011). More recently path analysis is considered a part of a more general method, structural equation modeling (Shipley 2002), with a new estimation methodology and more application possibilities; applications of such approach to path analysis are also becoming more and more popular in the agricultural sciences (e.g., Dhungana et al 2007, Kozak et al 2008. It is worth mentioning that criticism of path analysis is practically as old as the method itself (Niles 1923), and does not seem to stop.…”
Section: Interpreting Correlation Among Many Variablesmentioning
confidence: 99%